Development of Coated PLA Films Containing a Commercial Olive Leaf Extract for the Food Packaging Sector - Cecilia Fiorentini; Giulia Leni; Elena Díaz de Apodaca; Laura Fernández-; Gabriele Rocchetti; Claudia Cortimiglia; Giorgia Spigno; Andrea Bassani (MDPI AG, 2024)
A commercial olive leaf extract (OL), effective against Salmonella enterica, Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus, was added to three different coating formulations (methylcellulose, MC; chitosan, CT; and alginate, ALG) to produce active polylactic acid (PLA) coated films. Evaluation of these coated PLA films revealed significant inhibition of S. aureus growth, particularly with the MC and CT formulations exhibiting the highest inhibition rates (99.7%). The coated films were then tested for food contact compatibility with three food simulants (A: 10% ethanol; B: 3% acetic acid; D2: olive oil), selected to assess their suitability for pre-cut hams and ready-to-eat vegetables in relation to overall migration. However, coated films with active functions exhibited migration values in simulants A and B above legal limits, while promising results were obtained for simulant D2, highlighting the need to deeply investigate these coatings' impact on a real food system. Untargeted metabolomics revealed that the type of coating influenced the selective release of certain phenolic classes based on the food simulant tested. The Oxitest analysis of simulant D2 demonstrated that the MC and ALG-coated PLA films slightly slowed down the oxidation of this food simulant, which is an edible vegetable oil.